Ultrasound Diagnosis of Fetal Neck Masses: A Case Series - Shakina Rauff; Tan Eng Kien (Hindawi Limited, 2013)
Fetal neck masses are rare and may not be apparent during the second trimester fetal anomaly screening scan. It is essential to distinguish the different pathologies as it influences prenatal counseling, antenatal, and postnatal management. Furthermore, some causes may be amenable to in utero treatment. Others have a poor prognosis due to their association with congenital syndromes and aneuploidies. Differentiating the various neck masses and reaching an accurate diagnosis are a challenge. This requires a systematic approach, time and patience, together with an experienced sonographer. Ancillary investigations like karyotyping and magnetic resonance imaging may be used as well. It is important to attain an accurate diagnosis and to follow up the fetus with serial scans as this affects antenatal counselling and prognosis as well as the mode of delivery. Here, we present four cases of fetal neck masses that were seen at our antenatal diagnostic centre and highlight the distinguishing ultrasound features of each. This will enable one to approach the ultrasound diagnosis of fetal neck masses in a methodical and logical manner.